POLA KEPEMIMPINAN PADA PONDOK PESANTREN - Muhammad Arby Fahrezi; Amiruddin; Tiara Lubis; Salniati Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This literature research aims to compile and describe leadership patterns in Islamic boarding schools. The method used is the library research method. The data collection method used is the documentation method. The data analysis technique used is content analysis. To maintain the accuracy of the assessment and prevent errors in information in data analysis, cross-library checks are carried out and re-reading the literature and paying attention to the reviewer’s comments. The results of this study show that the figure of Kiai as a leader meets the ideal criteria. Kiai is trusted, obeyed and emulated by the community he leads, has high personal integrity towards truth, honesty and justice and really brings progress to the Islamic boarding school he leads.